(untitled) (South East Asia Journal of Public Health, 2013)
The nutritional status of children adversely affects their physical and mental growth. This study examined the nutritional status and morbidity pattern of government primary school children in north Kolkata of West Bengal, India. A cross-sectional study was conducted among 10 primary schools using interview techniques and anthropometric and clinical examinations. Of the 502 children, 40.2% children showed poor hygiene. The upper class students showed significantly poorer hygiene than that of lower class students. Anemia rate was 22.3% in these children and class II and III students showed significantly more anemia. Dental caries were found among 29.9% children and class II and III students showed significantly higher rate. About 10.4% children were found with enlarged tonsils and class I and III students showed higher prevalence. A major group of children (39.4%) gave the history of worm expulsion and the infestations of worms were observed significantly higher among lower class students. Vitamin B-complex deficit was observed among 20.7% and the deficiency was markedly observed among class II and IV students. Under-weight children were found in one-third of study population. There was no significant difference in nutrition among the participants from the various classes. There was no case of severe under-nutrition or stunting and wasting found in this study population. The findings of various nutritional status and morbidity patterns in this study highlight the needs to undertake various initiatives in relation to health promotion and prevention in primary schools. South East Asia J Public Health | Jan-June 2012 | Vol 2 Issue 1 | 13-17 DOI: http://dx.doi.org/10.3329/seajph.v2i1.15255